La scrittura di Cettina atoli Ajossa tra passioni tardoromantiche e presentimenti decadenti - Bombara, Daniela (Studia Romanica Posnaniensia, 2018)
The aim of this article is to bring to the attention of the scholars the writings of Cettina Natoli Ajossa (1867-1913), Sicilian noblewoman, who published several novels in which the Romantic paradigm is questioned and the crisis of the Nineteenth-Century world is highlighted. Particularly relevant the autobiographical memoir of Messina earthquake: it focuses upon the bitter conflict between classes, giving us the meaning of the end of an era.